PENGARUH PENGGUNAAN SECOND ACCOUNT INSTAGRAM TERHADAP TANGGUNG JAWAB DIGITAL MAHASISWA PPKN UNIVERSITAS LAMPUNG - Ferdian Syah; Yunisca Nurmalisa; Ana Mentari; Devi Sutrisno Putri; Elisa Seftriyana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of using a second Instagram account on the digital responsibility of Civics students at the University of Lampung. This research method uses a descriptive method with a quantitative approach. The research sample consisted of 76 students selected through a purposive sampling technique. Data collection used questionnaires and interviews, and data analysis used a simple linear regression test. The results of the study showed that using a second Instagram account had a positive and significant impact on digital responsibility by 31.5%, while the remaining 68.5% was influenced by factors outside the research variables. A second Instagram account can be a place of freedom while still being aware of the rules, as using a second account doesn't always have negative consequences if used for good purposes.